2017
DOI: 10.1007/s10943-017-0401-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Induced Bone Pain Management Through Buddhist Beliefs

Abstract: Dealing with physical pain represents a huge public health expenditure, especially for cancer-induced bone pain, one of the most difficult health issues, which impairs appetite, sleep, and mobility, negatively impacting quality of life and evoking mental problems. Although some literature has reported positive correlation between religion and pain management, there is a dearth of research examining the effectiveness of Buddhism on this topic. This study investigates the usefulness of Buddhist beliefs in managi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…Patients in hospice care who volunteered to practice Buddhist wisdom were found to have a decreased fear of death 38 . The same was found for a bone cancer patient 39 .…”
Section: The Association Between Nonself Desire and Death Anxiety: Fr...supporting
confidence: 79%
“…Patients in hospice care who volunteered to practice Buddhist wisdom were found to have a decreased fear of death 38 . The same was found for a bone cancer patient 39 .…”
Section: The Association Between Nonself Desire and Death Anxiety: Fr...supporting
confidence: 79%
“…CIBP is a most difficult pain condition [ 22 ]. It is estimated that approximately 60–84% of cancer patients are suffering from different degrees of bone pain [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buddhism has lower POF level than non-believers, positive religious coping styles in Buddhists' life signi ed an internalized secure spiritual relationship and well-integrated copying resources on which they could rely across a variety of stress situations [49] . Previous study have shown Buddhist beliefs could treat bone pain caused by cancer in a study conducted in Hong Kong, we infer that the Buddhists may also turn to their faith for coping using private prayer, meditation, or Chanting when facing uncontrollable fatigue related to endoscopy [50] .…”
Section: Discussionmentioning
confidence: 82%